2020
DOI: 10.1002/1878-0261.12662
|View full text |Cite
|
Sign up to set email alerts
|

PIM protein kinases regulate the level of the long noncoding RNA H19 to control stem cell gene transcription and modulate tumor growth

Abstract: The proviral integration site for Moloney murine leukemia virus (PIM) serine/threonine kinases have an oncogenic and prosurvival role in hematological and solid cancers. However, the mechanism by which these kinases drive tumor growth has not been completely elucidated. To determine the genes controlled by these protein kinases, we carried out a microarray analysis in T‐cell acute lymphoblastic leukemia (T‐ALL) comparing early progenitor (ETP‐ALL) cell lines whose growth is driven by PIM kinases to more mature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…Moreover, increased PIM1 levels were associated with worse prognosis [ 41 ] and poorer response to chemotherapy in these tumors [ 42 ]. PIM1 was also showed to promote highly aggressive, neuroendocrine variant of prostate cancer by epigenetic changes in H19, suggesting it may be implicated in malignant neuroendocrine transformation [ 13 ]. Our study for the first time indicated that PIM1 mRNA expression is significantly higher in SCLC samples than in other BP-NEN entities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, increased PIM1 levels were associated with worse prognosis [ 41 ] and poorer response to chemotherapy in these tumors [ 42 ]. PIM1 was also showed to promote highly aggressive, neuroendocrine variant of prostate cancer by epigenetic changes in H19, suggesting it may be implicated in malignant neuroendocrine transformation [ 13 ]. Our study for the first time indicated that PIM1 mRNA expression is significantly higher in SCLC samples than in other BP-NEN entities.…”
Section: Discussionmentioning
confidence: 99%
“…Protein kinases regulate many cellular signaling pathways, and their disruption is often associated with carcinogenesis [9]. Although dysregulations of the NEK2, PIM1, and PIM3 kinase signaling axes have been implicated in the pathogenesis of several cancers [10,11], including those with a neuroendocrine phenotype [12,13], their role in the pathogenesis of BP-NENs has not been determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The long non-coding RNA H19 also participates to the maintenance of the CSC pool. For instance, microarray analysis showed an increased expression of H19 and the pluripotent transcriptional factors Sox2, Oct4, and Nanog in the bulk acute lymphoblastic leukemia cells compared to early progenitors [66]. In addition, our team recently highlighted a stem cell gene signature (Aldh1a1+; CD44+/CD24−) in breast tumors expressing higher H19.…”
Section: H19 Contributes To the Enrichment And Maintenance Of Cscsmentioning
confidence: 97%
“…Furthermore, links between H19, CSCs, and drug resistance have also been established. In prostate CSCs, H19 expression has been shown to promote both resistance to the androgen deprivation therapy (ADT) and the induction of highly metastatic form of prostate cancer [66]. In glioblastoma, knockdown of H19 expression leads to decreased cellular proliferation and a higher apoptotic rate after induction by chemotherapy (temozolomide).…”
Section: H19 Enhances Drug Resistance Of Cscsmentioning
confidence: 99%